Utilization of global circulation models for climate change impacts assessments on agricultural water and crop production: a review - Mo'allim, Abdikani Abdullahi; Kamal, Md. Rowshon; Wayakok, Aimrun; Ahsan, Amimul; Mohamed, Abdirasak Ali; Moallim, Abdiaziz Abdullahi (Asian Online Journals, 2016)
Agricultural sectors are among the vulnerable areas which could be affected by the projected climatic change and associated global warming. Without adaption, climate change is commonly precarious for agriculture production, economies and communities dependent on agriculture. However, with appropriate adaption,vulnerabilities can be reduced and there are numerous opportunities to be realized. Therefore, it is critical to early find and prepare for adaptation strategies for various agro-systems in order to prevent adverse effects on water, crop production and economic conditions. In this review paper, we have summarized and compiled the effect of climatic change on irrigation water demands (IWR), crop evapotranspiration (ET) and crop yield production. The role of utilizing various Global Circulation Models for climate change impact studies was also included and tabulated.Climate changes may cause crop damages, low yield, and increased production cost resulting to income losses for farmers, grow their lower income level, and enhance their annual unemployment. Currently, the techniques to evaluate climate change consist of the statistical method computed from the historical data as well as the GCM simulation model. Nevertheless, various GCMs result in completely different results. Undoubtedly, there is uncertainty in any climate change analysis, thus, it's commended that several models need to be used where possible to prevent improper planning or adaptation responses especially in the near future.